Design, Simulation, and Experimental Verification of a Destruction Mechanism of Transient Electronic Devices. (31st December 2020) - Xiao, Yu; Zhang, Zhengyuan; Liao, Xiyi; Jiang, Feiyu; Wang, Yan
Abstract : To quickly destroy electronic devices and ensure information security, a destruction mechanism of transient electronic devices was designed in this paper. By placing the Ni-Cr film resistance and the energetic material between the chip and the package and heating the resistance by an electric current, the energetic material expanded and the chip cracked. The information on the chip was destroyed. The author simulated the temperature distribution and stress of the power-on structure in different sizes by ANSYS software. The simulation results indicate that the chip cracks within 50 ms under the trigger current of 0.5 A when a circular groove with an area of 1 mm 2 and depth of 0.1 mm is filled with an expansion material with an expansion coefficient of 10 −5 °C −1 . Then, the author prepared a sample for experimental verification. Experimental results show that the sample chip quickly cracks and fails within 10 ms under the trigger current of 1 A. The simulation and experimental results confirm the feasibility of the structure in quick destruction, which lays the foundation for developing instantaneous-failure integrated circuit products to meet information security applications.